Global War on Terror by the United States from the Perspective of International Humanitarian Law - Anggina, Lisa Novri (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Terrorism is used to intimidate the civilian population, influence government policies, and influence the organization of the state by means of kidnappings and killings. The terminology of terrorism itself is actually nothing new, until now terrorism remains an actual thing and continues to grow. Its development is in line with the development of human thought, science and technology and the development of high human movement between countries. These acts of terrorism are a global issue that affects the political policies of all countries in the world, making it a starting point for the perception to fight terrorism as an international enemy. In the War on Terror, the U.S. government is committing an